Work Posture analysis Using the Rapid Entire Body Method Assessment (REBA) to Reduce the Risk of Injury in Line I Employees Upper Production PT. XYZ - Jabbar, Karim Abdul; Suryadi, Akmal (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
This research aim to solve the problem of ergonomic standart in the process of making an upper shoes by implementing Rapid Entire Body Assessment (REBA). This method is suitable to solve job body posture problem of the worker of PT XYZ based in Sidoarjo. PT XYZ is an international company and one of the expantion company from Denmark, they produce high quality shoes with more than 7000 workers. There are several plaint from the worker that they had a featigue in some part of te body. REBA assess the score from the top of the body to the bottom of the body and giving report are report of the posture risk. By using this method, the solution can be found with giving the right posture of the worker body while working their duty. The result of the research are confirmed to reduce the risk of musculoskeletal disorders (MSDs) the posture need an improvement by changing the moves of trunk, upper arm, and wrist. Reba score are known in 6 and it’s increasing to 3 after the improvement.